Original paperEvaluation of different p16 immunostaining methods and the prognostic role of p16/Ki-67 combined expression in non-muscle invasive bladder cancers - Özyalvaçli, Gülzade; Özyalvaçli, Mehmet E.; Astarci, Hesna M.; Boran, Çetin; Yeşil, Cemile; Üyetürk, Ugur; Aktaș, Gülan (Polish Journal of Pathology, 2015)
There are many scoring methods evaluating the expression of p16 in the bladder immunohistochemically. In this study our aim was to determine an optimal p16 scoring method by discussing different staining methods related with p16 expression in bladder cancers and to establish the association of p16 and Ki-67 expressions, alone or in combination, with recurrence and progression. Ninety patients undergoing their first transurethral resection for bladder cancer and newly diagnosed papillary urothelial carcinoma (pTa and pT1) were included in the study. Four different scoring methods were used for p16 (p16a, p16b, p16c, p16d). The patients were divided into two groups based on recurrence and progression. There was a statistically significant difference between recurrence and abnormal p16d staining (p = 0.005). In other staining patterns of p16, there was no statistically significant difference in terms of recurrence or progression.In the multivariate logistic regression analysis, combined Ki-67 ≥ 10 and abnormal p16d staining was found to be the only independent predictive factor for recurrence (OR = 2.26, 95% CI: 0.13-46.41, p = 0.035) and no independent predictive factor for progression was found. Determining an adequate expression scoring by taking normal transitional epithelial staining pattern as a reference would be an objective approach in p16 evaluation. Moreover, it was found that evaluating p16d and Ki-67 in combination would be significant in predicting recurrence in pTa and pT1 urothelial carcinomas.